Comparative permeability of three saikosaponins and corresponding saikogenins in Caco-2 model by a validated UHPLC-MS/MS method - Siqi Ren; Jingjing Liu; Yunwen Xue; Mei Zhang; Qiwei Liu; Jie Xu; Zunjian Zhang; Rui Song (Elsevier, 2021)
Saikosaponins (SSs) are the main active components extracted from Bupleuri Radix (BR) which has been used as an important herbal drug in Asian countries for thousands of years. It has been reported that the intestinal bacteria plays an important role in the in vivo disposal of oral SSs. Although the deglycosylated derivatives (saikogenins, SGs) of SSs metabolized by the intestinal bacteria are speculated to be the main components absorbed into the blood after oral administration of SSs, no studies have been reported on the characteristics of SGs for their intestinal absorption, and those for SSs are also limited. Therefore, a rapid UHPLC-MS/MS method was developed to investigate and compare the apparent permeability of three common SSs (SSa, SSd, SSb2) and their corresponding SGs (SGF, SGG, SGD) through a bidirectional transport experiment on Caco-2 cell monolayer model. The method was validated according to the latest FDA guidelines and applied to quantify the six analytes in transport medium samples extracted via liquid-liquid extraction (LLE). The apparent permeability coefficient (Papp) determined in this study indicated that the permeability of SGs improved to the moderate class compared to the corresponding parent compounds, predicting a higher in vivo absorption. Moreover, the efflux ratio (ER) value demonstrated an active uptake of SSd and the three SGs, while a passive diffusion of SSa and SSb2.